Iodine-125 brachytherapy for orbital-invasive low-grade myxofibrosarcoma of the maxillary sinus: a case report challenging conventional therapeutic paradigms - Sun, Qiyu; Li, Shuai; Qiu, Quanli; Hu, Yanbo; Huang, Rui; Chen, Yan; Cui, Zhenzhen; Yang, Jiaxin; Ma, Xiaowen; Li, Min (Frontiers in Oncology, 2025)
Low-grade myxofibrosarcoma (LGMFS) is a rare subtype of soft tissue sarcoma, with an estimated incidence of approximately 0.18 cases per million population, accounting for about 0.6% of all soft tissue sarcomas. It is characterized by a high local recurrence rate and malignant potential. Orbital involvement secondary to maxillary sinus LGMFS represents an exceptionally rare occurrence. The management of such cases is complicated by anatomical complexity (e.g., proximity to optic nerve, lacrimal apparatus, and orbital vasculature) and limitations of conventional therapies, including radical resection combined with chemoradiation. In this anatomically complex case of recurrent Low-Grade Myxofibrosarcoma, iodine-125 brachytherapy achieved durable local control (12-month progression-free survival), demonstrating superior precision targeting and reduced systemic toxicity compared to conventional therapies. No acute radiation toxicity was observed, while facial swelling and eye pain were relieved with concurrent improvement in visual function.